2010
DOI: 10.1177/0042098009360224
|View full text |Cite
|
Sign up to set email alerts
|

Population Decline in Polish and Czech Cities during Post-socialism? Looking Behind the Official Statistics

Abstract: The evolving debate on "urban shrinkage" mirrors an increasing interest in demographic phenomena on the part of urban scholars. This paper discusses ambiguous evidence about recent population decline in the large cities of Poland and the Czech Republic, with a particular focus on Łódz and Brno in general and their inner cities more specifically. By applying a mixed-method approach, the paper identifies indications of inner-city repopulation and socio-demographic diversification which are not yet apparent in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…It should be noted, that the analysis of the movement of people between the cities is complicated because actual population size often does not correspond to the official statistical numbers. The researchers from Eastern Europe face the same challenge (Steinführer, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, that the analysis of the movement of people between the cities is complicated because actual population size often does not correspond to the official statistical numbers. The researchers from Eastern Europe face the same challenge (Steinführer, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Shortly thereafter it was described in the US in terms such as urban decline, urban decay or simply depopulation (Pallapst et al 2011). Urban researchers had to find comprehensive explanations for the variety of manifestations and conditions of decline, in addition to investigating its trajectories, conflicting interests, and hardly predictable trends (Martinez-Fernandez et al 2012;Steinführer et al 2010). There was a general lack of "(…) systematic empirical analysis of the crisis as a 'laboratory' for urban governance models" (Oosterlynck andGonzález 2013, p 1076).…”
Section: Urban Decline and The Context Of Post-industrial Us Citiesmentioning
confidence: 99%
“…At this point, it is also appropriate to highlight the problem of the comparability of statistical data in the metropolitan areas of post-socialist Central Europe related to the census data versus the annual population register. For example, Steinführer et al (2010) found the significant statistical variations in the measurements of the population size (influenced by suburbanization, intraregional and international labour out-migration, etc.) However, these impacts are negligible in terms of the results of our research.…”
Section: The Population Size Of the Metropolismentioning
confidence: 99%